Effect of Case Volume on Mortality After Pediatric Liver Transplantation in Korea. Issue 8 (August 2019) - Lee, Hannah; Jang, Eun Jin; Kim, Ga Hee; Yi, Nam Joon; Kim, Dal Ho; Yoo, Seokha; Row, Hyung Sang; Jung, Chul-Woo; Oh, Seung-Young; Ryu, Ho Geol
Abstract : Background: The purpose of this study was to evaluate whether institutional case-volume affects clinical outcomes after pediatric liver transplantation. Methods: We conducted a nationwide retrospective cohort study using the database of Korean National Healthcare Insurance Service. Between January 2007 and December 2016, 521 pediatric liver transplantations were performed at 22 centers in Korea. Centers were categorized according to the average annual number of liver transplantations: >10, 1 to 10, and <1. Results: In-hospital mortality rates in the high-, medium-, and low-volume centers were 5.8%, 12.5%, and 32.1%, respectively. After adjustment, in-hospital mortality was significantly higher in low-volume centers (adjusted odds ratio, 9.693; 95% confidence interval, 4.636-20.268; P < 0.001) and medium-volume centers (adjusted odds ratio, 3.393; 95% confidence interval, 1.980-5.813; P < 0.001) compared to high-volume centers. Long-term survival for up to 9 years was better in high-volume centers. Conclusions: Centers with higher case volume (>10 pediatric liver transplantations/y) had better outcomes after pediatric liver transplantation, including in-hospital mortality and long-term mortality, compared to centers with lower case volume (⩽10 liver transplantations/y).